2022
DOI: 10.1111/bcp.15394
|View full text |Cite
|
Sign up to set email alerts
|

Paracetamol dosing in hospital and on discharge for older people who are frail or have low body weight

Abstract: Aims To describe paracetamol dosing and liver function test (LFT) monitoring in older hospital inpatients who are frail or have low body weight. Methods Retrospective observational study, at a 790‐bed metropolitan public health service in Australia. Patients aged ≥70 years, with body weight <50 kg or frailty index based on laboratory data (FI‐Lab) score ≥0.3, who were administered paracetamol during an admission with length‐of‐stay >72 hours, were included. Data were extracted from electronic medical records. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 49 publications
1
7
0
Order By: Relevance
“…Our research suggests dose adjustment of acetaminophen was uncommon when our data were collected in 2019. Our findings are comparable with another Australian study in 2019 that reported 150 (62.5%) of 240 older hospital inpatients were prescribed acetaminophen at higher than recommended doses (> 3000 mg/day or ≥ 60 mg/kg/day for patients with a body weight < 50 kg) [ 35 ]. Overall, 18.8% of residents received opioid doses > 60 MME/day.…”
Section: Discussionsupporting
confidence: 88%
“…Our research suggests dose adjustment of acetaminophen was uncommon when our data were collected in 2019. Our findings are comparable with another Australian study in 2019 that reported 150 (62.5%) of 240 older hospital inpatients were prescribed acetaminophen at higher than recommended doses (> 3000 mg/day or ≥ 60 mg/kg/day for patients with a body weight < 50 kg) [ 35 ]. Overall, 18.8% of residents received opioid doses > 60 MME/day.…”
Section: Discussionsupporting
confidence: 88%
“…As paracetamol is not associated with significant adverse effects than traditional nonsteroidal anti‐inflammatory drugs, paracetamol is recommended as first‐line therapy for the management of pain in older adults. Likewise, some studies reported paracetamol regimens in older adults that involved administrations >3 or 4 g/d 2,17,18 . In a French study, 50% of patients aged >75 years with risk factor for toxicity (low body weight or malnutrition) had their paracetamol dose not reduced 17 .…”
Section: Discussionmentioning
confidence: 99%
“…As paracetamol was considered safe at therapeutic doses, it has been recommended as a first‐line drug in pain management guidelines, especially for aged and frail patients 4 . However, the pharmacokinetic of paracetamol may be influenced by physiological and pathological changes in older patients, especially those who are underweight or frail 2 . Studies have reported a reduction of paracetamol clearance with aging and frailty, resulting in an increase of paracetamol serum levels 5,6 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations